PEMODELAN BANJIR DI DAS CILIWUNG MENGGUNAKAN MODEL HIDROLOGI TERDISTRIBUSI - Ratih Indri Hapsari, Mohamad Zenurianto, Hari Kurnia Safitri, Agus Suhardono (Prokons: Jurnal Teknik Sipil, 2016)
Jakarta, the capital and largest city in Indonesia, suffered severe flood year by year. The flooding was greatly contributed by high runoff in Ciliwung River, the main river flowing through Jakarta. In this paper, the attempt to simulate the flood in Ciliwung River using distributed hydrological model is presented. Precipitation reanalysis at spatial and temporal resolutions of one degree and one hour from Jaxa Global Rainfall Watch is used for evaluating the rainfall within the basin (376 km2). Understanding the characteristic of rainfall-runoff mechanisms is important as a lesson learnt for future flood disaster mitigation. The model used in this research is BTOPMC physically distributed hydrological model, which uses blockwise TOPMODEL for runoff generation and Muskingum-Cunge for routing. Terrain map of study area with 30 meters resolution is obtained from ASTER-GDEM. The runoff is simulated hourly in three points, i.e. Katulampa, Depok, and MT. Haryono, representing upstream, middle stream, and downstream outlets. Validation by comparison with observed discharge is done in both points. The results reveal that the model gives reasonable results in simulating flood events, showed by NSE and RMSE at Katulampa of 56.81% and 87.58 m3/s. This simulation is useful to estimate the amount and timing of flooding which is essential for further application in flood forecasting and disaster risk management. Some further improvements of the simulation scheme, including utilization of radar-rainfall, field survey, and future direction for flood forecasting and warning system development are also discussed.Keywords: Flood, Ciliwung, Jakarta, Hydrological Model